An Analysis of Narrative Structure in Interstellar and Ready Player One - Danu Ilham Akbar (LPPM Universitas Bumigora Mataram, 2023)
This article explores science fiction films, a popular genre known for its depiction of technology as a symbol of the future. The future depicted in these science fiction films is a sign of hope and critics of a particular social problem. Using Interstellar and Ready Player One as case studies, this research aims to explore the broader and deeper meanings conveyed through the narrative structure of the films, including language, issues discussed, and the use of other elements. The analysis uses a qualitative method, which involves observing the movie, recording important data, and connecting the narrative with visual aspects. The research reveals how narrative and visual elements complement each other to create a memorable cinematic experience. The results show that Interstellar is identified as a science fiction film rooted in scientific principles, with a focus on space exploration and time dilation. Ready Player One, on the other hand, leans more towards fantasy, incorporating virtual reality and magical elements. Despite this difference, both movies are considered science fiction, as fantasy shares elements with the genre.